The Impact of Artificial Intelligence on Cycle 1 Public School Students in Abu Dhabi - AL-JABERI, MAITHA SALEM (2023)
The abstract of this dissertation is to understand the impact of artificial intelligence (AI) on education while investigating the opinions of the three main stakeholders of education parents, teachers, and school leadership. The study is based in the United Arab Emirates and specifically the capital Abu Dhabi. Moreover, the research findings circulate cycle 1 learners in public schools, ages of these students start from four to eleven years old, and how this advanced tool (AI) can affect their learning. The aim of this research was to get a better understanding of how AI can affect students’ learning and how integration at such a young age might affect them psychologically. The researcher used a mixed-method approach where they combined both quantitative and qualitative research methods. Online surveys were distributed between cycle 1 teachers, school leadership, and parents who have children in the cycle 1 public school and that reside in Abu Dhabi. Face to face interviews were conducted by the researcher, two participants from each category. One of the major findings of this research was that all participants encourage the integration of this tool but share concerns about the safety of these children. With AI being such an advanced tool and always changing with new approaches, how can this affect their learning process and match the 21st century ‘skills the students are learning. Another major finding from the study was how will be the role of teachers, parents and school leadership might change. AI can be very useful for teachers as they can help them to reduce their workload, for school leadership to automate data and allocate resources and for the students to self-direct their learning by asking virtual tutors for extra support at home. Overall, the conclusion of this study is that AI can be a very helpful tool to be introduced very early on in a student’s learning journey without any continuous guidance, but it can also contain some dangers. As much as AI is very new and still being researched by educators all over the world it can be a great addition in the education field.